A targeted method for standardized assessment of adverse drug events in surgical patients. Issue 6 (18th April 2013) - de, Monica; Kiewiet, Jordy J. S.; Boeker, Eveline B.; Ramrattan, Maya A.; Dijkgraaf, Marcel G. W.; Lie‐A‐Huen, Loraine; Boermeester, Marja A.; ,
Abstract Objectives This study demonstrates the development, reliability and outcome of a targeted method for standardized assessment of adverse drug events (ADEs) in surgical patients. Methods Initial practice evaluation of this ADE assessment method was carried out in a prospective single centre cohort study. In total, 262 electively admitted surgical patients were included. The surgical trigger tool was applied to patients' medical records by two independent reviewers, and subsequent assessment of causality, severity and preventability of ADEs was carried out by two independent expert panels consisting of a consultant surgeon and a clinical pharmacologist. The surgical trigger tool and causality assessment method were each tested on reliability in a separate group of 50 randomly selected patients using Fleiss and Cohen's kappa statistics and percentages of agreement. Comparison of this method with an existing trigger tool method for ADEs was performed. Results Our surgical trigger tool contains 51 triggers. The inter‐ and intra‐rater calculations showed substantial to almost perfect levels of agreement (kappa range 0.71–0.83), with a 97.8–98.5% percentage of agreement. Fair to substantial levels of agreement were calculated for causality, severity and preventability (kappa range 0.38–0.79). The percentages of inter‐ and intra‐rater agreement were 68.9 and 70.5% for causality, 67.0 and 82.0% for severity, and both 98.4% for preventability, respectively. Compared with the existing trigger tool method for ADEs, we found an additional 363 triggers, 18 ADEs (an extra 20%) and 3 preventable ADEs in our surgical cohort. Conclusions This targeted trigger tool for standardized assessment of ADEs in surgical patients shows excellent agreement between reviewers. The assessment of medication‐related harm had acceptable agreement. Compared with an existing ADE trigger tool method, the present method found almost 20% extra ADEs. This method can be a useful alternative to existing trigger tool methods, in particular to assess medication safety in surgical patients.